The UK-Rwanda Migration and Economic Development Partnership Based on International Refugee Law - Susanto, Fransiska Ayulistya (PADJADJARAN JURNAL ILMU HUKUM (JOURNAL OF LAW), 2025)
On April 14, 2022, British Prime Minister Boris Johnson announced intentions to deport Rwandan asylum seekers arriving by small boats. Under this arrangement, individuals who sought protection but were later deemed unsuitable and undesirable by the UK would be re-transported to Rwanda, where Rwandan authorities would review their claims. This Policy was rejected by several asylum and refugee organizations, which argued that it was inhumane and would only imprison asylum seekers before sending them to countries where they faced torture or persecution. This study employed sociolegal analysis and combined doctrinal research with an empirical approach. It used secondary sources, such as government statements, reports, articles, and news reports. The result explains the UK and Rwanda Memorandum of Understanding on Migration, the development of the policy, and how international law view it. This study provides evidence that the UK has violated international law by implementing the partnership plan with Rwanda. The bilateral transfer arrangement is incompatible with or violates Article 31, 33 (1) of the 1951 Refugee Convention; and Article 3 of the European Convention on Human Rights. Furthermore, Rwanda has failed to meet the conditions for accommodation and to ensure its safety from deportation, persecution, or other human rights abuses committed by its residents and the government.